Sex-Specific Effects of Synbiotic Exposure in Mice on Addictive-Like Behavioral Alterations Induced by Chronic Alcohol Intake Are Associated With Changes in Specific Gut Bacterial Taxa and Brain Tryptophan Metabolism - Pizarro, Nieves; Kossatz, Elk; González, Pedro; Gamero, Alba; Veza, Emma; Fernández, Cristina; Gabaldón, Toni; de la Torre, Rafael; Robledo, Patricia (Frontiers in Nutrition, 2021)
Chronic alcohol intake has been shown to disrupt gut microbiota homeostasis, but whether microbiota modulation could prevent behavioral alterations associated with chronic alcohol intake remains unknown. We investigated the effects of synbiotic dietary supplementation on the development of alcohol-related addictive behavior in female and male mice and evaluated whether these effects were associated with changes in bacterial species abundance, short-chain fatty acids, tryptophan metabolism, and neurotransmitter levels in the prefrontal cortex and hippocampus. Chronic intermittent exposure to alcohol during 20 days induced escalation of intake in both female and male mice. Following alcohol deprivation, relapse-like behavior was observed in both sexes, but anxiogenic and cognitive deficits were present only in females. Synbiotic treatment reduced escalation and relapse to alcohol intake in females and males. In addition, the anxiogenic-like state and cognitive deficits observed in females following alcohol deprivation were abolished in mice exposed to synbiotic. Alcohol-induced differential alterations in microbial diversity and abundance in both sexes. In females, synbiotic exposure abrogated the alterations provoked by alcohol in Prevotellaceae UCG-001 and Ruminococcaceae UCG-014 abundance. In males, synbiotic exposure restored the changes induced by alcohol in Akkermansia and Muribaculum uncultured bacterium abundance. Following alcohol withdrawal, tryptophan metabolites, noradrenaline, dopamine, and γ-aminobutyric acid concentrations in the prefrontal cortex and the hippocampus were correlated with bacterial abundance and behavioral alterations in a sex-dependent manner. These results suggested that a dietary intervention with a synbiotic to reduce gut dysbiosis during chronic alcohol intake may impact differently the gut-brain-axis in females and males.